Efficacy of mucosal vaccination using a protozoan parasite as a vehicle for antigen delivery: IgG and neutralizing response after rectal administration of LeCoVax-2, a candidate vaccine against COVID-19. (December 2022) - Epis, Sara; Varotto-Boccazzi, Ilaria; Manenti, Alessandro; Rubolini, Diego; Gabrieli, Paolo; Cattaneo, Giulia Maria; Gourlay, Louise; Dapporto, Francesca; Monti, Martina; Razzano, Ilaria; Leonardi, Margherita; Iannacone, Matteo; et al.
Abstract: Mucosal vaccination is regarded as a promising alternative to classical, intramuscular vaccine delivery. However, only a limited number of vaccines have been licensed for mucosal administration in humans. Here we propose Leishmania tarentolae, a protozoan parasite, as a potential antigen vehicle for mucosal vaccination, for administration via the rectal or oral routes. To test this hypothesis, we exploited L. tarentolae for the production and delivery of SARS-CoV-2 antigens. Two antigens were assayed in BALB/c mice: Lt-spike, a L. tarentolae clone engineered for the surface expression of the SARS-CoV-2 spike protein; RBD-SD1, a purified portion of the spike protein, produced by another engineered clone of the protozoon . Immune response parameters were then determined at different time points. Both antigens, administered either separately or in combination (Lt-spike + RBD-SD1, hereafter LeCoVax-2), determined significant IgG seroconversion and production of neutralizing antibodies after subcutaneous administration, but only in the presence of adjuvants. After rectal administration, the purified RBD-SD1 antigen did not induce any detectable immune response, in comparison with the intense response observed after administration of LeCoVax-2 or Lt-spike alone. In rectal administration, LeCoVax-2 was also effective when administered without adjuvant. Our results show that L. tarentolae is an efficient and safe scaffold for production and delivery of viral antigens, to be used as vaccines. In addition, rectal vaccination experiments prove that L. tarentolae is suitable as a vaccine vehicle and adjuvant for enteral vaccination. Finally, the combined preparation LeCoVax-2 can be considered as a promising candidate vaccine against SARS-CoV-2, worthy of further investigation. Graphical Abstract: ga1 Highlights: The protozoan parasite Leishmania tarentolae is proposed as a vehicle for mucosal vaccination. LeCoVax-2: Leishmania tarentolae expressing SARS-CoV-2 virus spike protein, co-administered with the purified RBD protein. In murine models, both subcutaneous and rectal administration of LeCoVax-2 determine the production of specific antibody responses, endowed with viral-neutralizing activity. Leishmania tarentolae holds great potential as a vaccine vehicle and adjuvant, for vaccination through the enteral route. LeCoVax-2 merits further investigation, in the context of the efforts towards the development of COVID-19 mucosal vaccines.